Hubungan Efikasi Diri dengan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Siswa di SMK Swasta Pembangunan Bukittinggi - Yora Nurhazizah; Iswantir Iswantir (Lembaga Yasin AlSys, 2026)
Although the relationship between self-efficacy and learning outcomes has been widely discussed in various studies, studies that specifically examine the relationship between self-efficacy and learning outcomes in Islamic Religious Education and Character Education (PAI and BP) among vocational high school students remain limited. This study aims to determine the relationship between self-efficacy and PAI and BP learning outcomes among students at SMK Swasta Pembangunan Bukittinggi. This study employed a quantitative approach with a correlational design, involving 60 students selected through total sampling. Data were collected using a questionnaire to measure self-efficacy and score documentation to measure learning outcomes, and were then analyzed using the Spearman Rank correlation technique. The results showed that there was a positive and significant relationship between self-efficacy and learning outcomes, with a correlation coefficient of 0.264 and a significance value of 0.042 (< 0.05). These findings indicate that students with higher self-efficacy tend to have better learning outcomes, although the level of relationship found was in the low category. This study contributes to strengthening self-efficacy theory in the context of PAI and BP learning and broadens understanding of the role of psychological factors in the achievement of vocational high school students’ learning outcomes. The conclusion of this study confirms that self-efficacy is one of the factors that contributes to students’ learning success. Therefore, teachers and educational institutions need to develop learning strategies that can enhance students’ self-efficacy. The implications of this study include theoretical contributions to the field of educational psychology and practical contributions to the development of character-based learning, while also opening opportunities for further research on other factors that influence student learning outcomes.